2017
DOI: 10.3390/md15040112
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Wound Healing Using Low Molecular Weight Fucoidan in a Full-Thickness Dermal Excision Rat Model

Abstract: Low molecular weight fucoidan (LMF) has been reported to possess anti-inflammatory and antioxidant activities. Thus, we examined the effects of LMF extracted from Undaria pinnatifida on dermal wounds. Five round dermal wounds were created on the dorsal back of rats, and they were then treated topically with distilled water (DW), Madecasol Care™ (MC) or LMF at 200, 100 and 50 mg/mL, twice a day for a week. There were dose-dependent increases in wound contraction in the groups receiving LMF but not in the MC gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 53 publications
3
47
0
3
Order By: Relevance
“…Future experiments will focus on the early phases of this inflammatory process, in particular the kinetics of neutrophil recruitment to the infected footpad and DRG neurons. It would be interesting to assess the therapeutic efficacy of inhibitors of neutrophil recruitment, such as fucoidan, on the immunopathology of PRV in mice (62).…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments will focus on the early phases of this inflammatory process, in particular the kinetics of neutrophil recruitment to the infected footpad and DRG neurons. It would be interesting to assess the therapeutic efficacy of inhibitors of neutrophil recruitment, such as fucoidan, on the immunopathology of PRV in mice (62).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [133] investigated the wound healing properties of alginate in the treatment of full-thickness skin defects in rats and found significant decrease of wound sizes in alginate treated groups. Fucoidan alone or in combination with chitosan also showed the best reepithelization and fastest wound closure results in rabbit dermal burns [134]. On the other hand, Custódio et al [135] have shown that laminarin can be used for the formation of biocompatible, mechanically stable and injectable hydrogels that can be used for soft tissue repair.…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 99%
“…Therefore, this study demonstrated apparent anti-bacterial and cutaneous wound healing effects of fucoidan. Fucoidan is known for its anti-bacterial, anti-viral, immunostimulatory, and healing stimulating effects [2][3][4][5][6][7][8][9][10][11]. In a previous study, fucoidan inhibited the growth of Staphylococcus aureus and Escherichia coli [5].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan was also used as a prevention and treatment measure to control diseases caused by Helicobacter pylori [4]. Similutaneously, previous liteature demonstrated the cutaneous wound healing effect of fucoidan [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation